Analysis of Forming Limit Diagram for Ti-6Al-4 V Alloy. (2015) - Kotkunde, Nitin; Gupta, Amit Kumar
Abstract: Forming limit diagram (FLD) is aplotofthelimitingprincipalsurfacestrainsthatcanbesustainedby sheet metalspriortotheonsetoflocalized necking. It isusefulforcharacterizingtheformabilityofsheet metal and assessingtheformingseverityofvarious sheet metal processes. In this work, experimental FLD has been determined for Ti-6Al-4 V alloy at 400 0 C using Nakajima test. Nakajima test has been conducted using spherical punch with specimens of different widths as per ASTM: E2218 – 02standard. In order to validate the experimental FLD results, theoretical forming limit diagram has been determined using MarciniakKuczynski (M-K) model. The accuracy of theoretical FLD is largely dependent on the selection yield criteria and hardening models. Here in M-K analysis, CazacuBarlat yield criterion with Hollomon power law (HPL) and Johnson-Cook (JC) hardening model has been considered. The material properties required for determination of yield criteria and hardening models have been calculated using uniaxial tensile tests. The predicted theoretical FLD results have been compared with experimental FLD. The influences of yield criteria and hardening models on the M-K theory parameters and the prediction itself have been investigated in the process. Based on the results; it can be observed that the theoretical FLD using CazacuBarlat with both hardening models has a better agreement with experimental FLD.